The Routledge International Handbook of Engineering Ethics Education - Chance, Shannon; Børsen, Tom; Adela Martin, Diana; Tormey, Roland; Taro Lennerfors, Thomas; Bombaerts, Gunter (Routledge International Handbooks of Education, 2025)
Responding to the need for a timely and authoritative volume dedicated to this burgeoning and expansive area of research, this handbook will provide readers with a map of themes, topics, and arguments in the field of engineering ethics education (EEE). Featuring critical discussion, research collaboration, and a team of international contributors of globally recognized standing, this volume comprises six key sections which elaborate on the foundations of EEE, teaching methods, accreditation and assessment, and interdisciplinary contributions. Over 100 researchers of EEE from around the globe consider the field from the perspectives of teaching, research, philosophy, and administration. The chapters cover fast-moving topics central to our current understanding of the world such as the general data protection regulation (GDPR), artificial intelligence (AI), biotechnology, and ChatGPT; and they offer new insights into best practices research to equip program leaders and instructors delivering ethics content to students. This Open Access volume will be of interest to researchers, scholars, postgraduate students, and faculty involved with engineering education, engineering ethics, and philosophy of education. Curriculum designers, staff developers teaching pedagogical courses to faculty, and engineering professionals may also benefit from this volume. The Open Access version of this book, available at http://www.taylorfrancis.com, has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives (CC-BY-NC-ND) 4.0 license.